Organising Inclusive Transitions in Vocational Education and Training in a Rural Community in Norway - Rapp, Anna; Knutas, Agneta (Australian and International Journal of Rural Education, 2024)
Our study examines the organising of transitions in Vocational Education and Training in a rural Norwegian municipality. In Norway, Vocational Education and Training is diverse and interlinked in continual organising. Organising, in this context, is a continuous set of actions forming recognisable patterns that become institutions. An upper secondary Vocational Education and Training case study was conducted in a rural municipality. The case study included interviews with students, teachers, leaders and company representatives. The study investigated in what ways the organising of rural Vocational Education and Training supported students’ crossroads and transitions to limit marginalisation. The findings indicate that actants in the network, as well as a balance between individuals’ needs and labour market requirements, are stabilising factors. The interdisciplinary training office is an important choreographer in active networking, and it is also important for teachers and students to bridge over and interact with Vocational Education and Training companies early on in their education. Transition as a path to inclusion is a learning and developmental process that occurs in continuous, alternating interactions between education and work.